THE ABILITY OF STATISTICAL LITERACY STUDENT TEACHER CANDIDATE IN TERMS OF PRIOR-ABILITY ON MATHEMATICS - Johannis Takaria; Melvie Talakua (Jurnal Kependidikan, 2018)
This study was aimed at analyzing the difference improvement of statistical literacy of the student teacher candidate in terms of their prior-ability on mathematics (PAM). This study used the Quasi Experiment method with the Non-equivalent Pretest-Posttest Control Group type and a sample of seventy elementary school student teacher candidates. The sampling technique used was purposive sampling method. The results of the research data were then analyzed using an independent sample t-test. Normalized-gain was used to analyze the improvement of students’ statistic literacy abilities. The study results significant differences in statistical literacy. Based on PAM, the group of students who received collaborative problem solving (CPS) models achieved higher statistical literacy improvements than students in the expository group. The improvement of statistical literacy was due to the effectiveness of CPS model. Collaborating can strengthen student statistic literacy skills. The ability of statistical literacy in learning requires students to have good PAM, because the PAM is a combination of knowledge and mathematical thinking skills in collaborating students can be actively involved in dealing with solving challenging statistical problems.KEMAMPUAN LITERASI STATISTIK MAHASISWA CALON GURU DITINJAU DARI KEMAMPUAN AWAL MATEMATIKAAbstrakPenelitian ini bertujuan untuk menganalisis perbedaan peningkatan literasi statistis mahasiswa ditinjau dari kemampuan awal matematis (KAM). Penelitian menggunakan metode Quasi Eksperiment dengan tipe Non equivalent Pretest-Posttest Control Group. Sampel sebanyak 70 mahasiswa calon guru sekolah dasar yang diambil menggunakan metode purposive sampling. Data dianalisis menggunakan uji independent sample t-test. Normalized-gain digunakan untuk menganalisis peningkatan kemampuan literasi statistis mahasiswa. Penelitian menghasilkan adanya perbedaan signifikan peningkatan literasi statistis. Berdasarkan KAM kelompok mahasiswa yang mendapatkan pembelajaran dengan model collaborative problem solving (CPS) mencapai peningkatan literasi statistis lebih tinggi dari mahasiswa pada kelompok ekspositori. Peningkatan literasi statistis dikarenakan efektifnya penggunaan model CPS. Berkolaborasi dapat memperkuat kemampuan literasi statistis mahasiswa. Kemampuan literasi statistis dalam pembelajaran mensyaratkan mahasiswa harus memiliki KAM yang baik, karena KAM merupakan kombinasi antara pengetahuan dan keterampilan berpikir matematis sehingga dalam berkolaborasi mahasiswa dapat terlibat aktif dalam menghadapi dan menyelesaikan masalah statistik yang menantang.